PERLINDUNGAN HAK KEPERDATAAN TERHADAP ANAK AKIBAT PEMBATALAN PERKAWINAN SETELAH SALAH SATU PIHAK MENINGGAL - Syafiqa Tiara Ayunda; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The issue of canceling a marriage might be not that common in Indonesia Citizens. But cases like this are already common in big cities. The cancellation of the marriage is due to the non-fulfillment of the conditions of the marriage or violation of the marriage ban which is written in Law Number 1 of 1974 concerning Marriage by person who do not consider marriage as a sacred thing that must be met in order to be legal and sacred. Cancellation of marriage itself can be detrimental to various parties in the future.The purpose of this study is to determine the legal consequences of a marriage cancellation in which one party dies and the fulfillment of children's rights as a result of a marriage cancellation after one of the parties dies. This type of research is normative legal research or what is known as